2023
DOI: 10.3390/jof9020150
|View full text |Cite
|
Sign up to set email alerts
|

Four New Species of Torula (Torulaceae, Pleosporales) from Sichuan, China

Abstract: Torula is an asexual and hyphomycetous genus in the family Torulaceae. Torula species are generally saprophytic. They have a worldwide distribution and abound in humid or freshwater habitats. In order to better understand this genus, we carried out several field collections from Sichuan, China. As a result, we obtained nine Torula isolates from dead woody substrates in terrestrial and freshwater habitats. Based on a biphasic approach of morphological examination and multi-locus phylogenetic analyses (ITS, SSU,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 46 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…3 ). Morphological characteristics of our new collection are consistent with Torula submersa ( Tian et al 2023 ). Based on morphological characteristics and phylogenetic analysis, we, therefore, identified our new collection as Torula submersa , which was collected from a lentic freshwater habitat for the first time.…”
Section: Taxon Treatmentssupporting
confidence: 71%
See 3 more Smart Citations
“…3 ). Morphological characteristics of our new collection are consistent with Torula submersa ( Tian et al 2023 ). Based on morphological characteristics and phylogenetic analysis, we, therefore, identified our new collection as Torula submersa , which was collected from a lentic freshwater habitat for the first time.…”
Section: Taxon Treatmentssupporting
confidence: 71%
“…Taxonomic research on Torulaceae in China is mainly concentrated in the south-western region and commonly found in freshwater habitats ( Hyde et al 2016 , Su et al 2016 , Su et al 2018 , Qiu et al 2022 , Tian et al 2023 ). There are four genera of Torulaceae viz.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most Torula species have been reported from terrestrial habitats, with only nine species reported from freshwater habitats, and four species viz. T. fici , T. gaodangensis , T. mackenziei and T. masonii have been found in both terrestrial and freshwater habitats ( Su et al 2018 ; Hyde et al 2020 ; Boonmee et al 2021 ; Tian et al 2023 ).…”
Section: Introductionmentioning
confidence: 99%